TAMAN PERAGA DAN EKSPLORASI SAINS TEKNOLOGI SEBAGAI ICON IPTEK DI BANDUNG DENGAN PENDEKATAN ARSITEKTUR METAFORA - Adinda Putri Putri; Agung Kumoro Kumoro; Ana Hardiana Hardiana (Universitas Sebelas Maret Surakarta, 2014)
Abstract: Exhibit and Exploration of Technology Science Park are facility that aims to introduce, enrich knowledge, and create new things about science and technology. Main purpose of this building is to make grow an appreciation of science and technology for society with their all ages category easily and memorable, through a variety of activities that involve many kinds of interactive exhibition which can be used easily. The building design concept which is planned by developing the technological sophistication and structural using are dominant of the use of the fabrication materials of interior, exterior, and structure elements. Starting from the empirical character of science and technology, rational, systematic and dynamic, Exhibit and Exploration of Technology Science buildings realized in the form of images that are constantly developing and emphasize technology sophistications to reinforce its image as an icon of science and technology. By using the metaphor of architectural approach, ‘the history of technology’ Bandung city will be displayed into an Exhibit and Exploration of Technology Science building. So, people who visit this region will remember that Bandung is a city of technology. Keywords: Exhibit and exploration of science and technology park, icon of science and technology, metaphor architecture